Mesh Construction Algorithm Based on TetGen for Modeling the External Flow Around an Axisymmetric Model - Shirokov, I. A. (Mathematical models and computer simulations, 2021)
An original algorithm for constructing a computational grid for modeling an external gas-dynamic flow around an axisymmetric model using a TetGen mesh generator is described. The algorithm gives opportunity to construct unstructured tetrahedral meshes in space around the model in such a way that the cells near the surface have a shape close to regular tetrahedra. On such meshes, the approximation of macroscopic equations is more accurate than on meshes containing tetrahedral cells with small angles. The increased accuracy of approximation in the boundary layer region can be an important factor in studying the phenomena of flow separation and laminar-turbulent transition. To construct such a spatial grid, at the initial stage, a grid is built on the surface of the model, the cells of which have a shape close to squares. At the second stage, based on the surface grid, the TetGen generator builds a spatial tetrahedral mesh using the Delaunay triangulation, while additional points are introduced near the model surface, which make it possible to obtain tetrahedral cells of a fairly regular shape in the boundary layer region. The proposed algorithm is quite universal and can be used for models of an arbitrary axisymmetric shape, the profile of which is specified as an array of radius values depending on the cross section. The spatial mesh allows modeling the external flow for nonzero angles of attack. An example of calculating a subsonic flow around a model based on a quasi-gasdynamic algorithm, demonstrating the appearance of a vortex section in the tail section, is given. This section shows the possibility of studying unsteady flows.